2017
DOI: 10.1016/j.scitotenv.2017.05.279
|View full text |Cite
|
Sign up to set email alerts
|

The true costs of participatory sanitation: Evidence from community-led total sanitation studies in Ghana and Ethiopia

Abstract: Evidence on sanitation and hygiene program costs is used for many purposes. The few studies that report costs use top-down costing methods that are inaccurate and inappropriate. Community-led total sanitation (CLTS) is a participatory behavior-change approach that presents difficulties for cost analysis. We used implementation tracking and bottom-up, activity-based costing to assess the process, program costs, and local investments for four CLTS interventions in Ghana and Ethiopia. Data collection included imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 18 publications
3
25
1
Order By: Relevance
“…While curricula for safety trainings covered all EHS simultaneously, we included the full training costs under each EHS, as each EHS required annual training and costs would not be substantially reduced by removing irrelevant curricula. Waste management had additional costs associated with consumables and capital maintenance for waste transport vehicles, which we estimated using established methods [37].…”
Section: Costs Data Collectionmentioning
confidence: 99%
“…While curricula for safety trainings covered all EHS simultaneously, we included the full training costs under each EHS, as each EHS required annual training and costs would not be substantially reduced by removing irrelevant curricula. Waste management had additional costs associated with consumables and capital maintenance for waste transport vehicles, which we estimated using established methods [37].…”
Section: Costs Data Collectionmentioning
confidence: 99%
“…We can refer to the following "family" of four articles on CLTS in Ethiopia and Ghana (Crocker et al 2016a;2016b;2017a;2017b):…”
Section: Examples Of Primary Studiesmentioning
confidence: 99%
“…The fourth study byCrocker et al (2017b) once again considered the same interventions in Ethiopia and Ghana but reported on the costs of their implementation disaggregated by various parameters rather than on their results.…”
mentioning
confidence: 99%
“…Second-round revisions were informed by approximately 1000 hours of field experience across all authors in 12 countries in the World Bank regions for Latin America and the Caribbean, Middle East and North Africa, and Sub-Saharan Africa. For selected published examples, see [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We identified good practices of studies that scored highly in risk of bias assessments compared to studies with low scores (see [15] for details). Additionally, we reviewed selected guidelines for EHS delivery in HCFs [8,[24][25][26][27], costing studies of EHS from non-HCF contexts [23,28,29], guidelines for costing healthcare and HCFs [18,30], and reporting standards for costing [31,32].…”
Section: Introductionmentioning
confidence: 99%